2005
DOI: 10.1046/j.1540-8167.2005.40513.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Right Atrial Substrate in Patients with Supraventricular Tachyarrhythmias

Abstract: Negative unipolar voltage analysis of global RA showed different RA substrate characteristics during various SVT. The substrate property of activation and cycle length-dependent voltage reduction may be related to the development of AFL and AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 30 publications
1
69
2
Order By: Relevance
“…A previous study reported that the electrogram voltage distribution in the right atrium was functionally dependent on the cycle lengths (Lin et al 2005). However, in the present study, a low voltage in the septum in the patients with AFL could be found in comparison to those without AFL even during pacing at a cycle length of 600 msec from the CSO after creating conduction block in the isthmus between the IVC and TA, which might indicate the electrophysiological properties of the RA septum.…”
Section: Mechanism Of the Electrophysiological Properties In The Righcontrasting
confidence: 71%
See 2 more Smart Citations
“…A previous study reported that the electrogram voltage distribution in the right atrium was functionally dependent on the cycle lengths (Lin et al 2005). However, in the present study, a low voltage in the septum in the patients with AFL could be found in comparison to those without AFL even during pacing at a cycle length of 600 msec from the CSO after creating conduction block in the isthmus between the IVC and TA, which might indicate the electrophysiological properties of the RA septum.…”
Section: Mechanism Of the Electrophysiological Properties In The Righcontrasting
confidence: 71%
“…However, there has been some controversy as to the exact location of the area of slow conduction within the AFL circuit. Furthermore, the mean unipolar electrogram voltage of the global RA using a noncontact mapping system is significantly decreased during AFL as compared with sinus rhythm and this reduction has been noted in the lower septum as well as the CT and isthmus between the IVC and TA (Lin et al 2005). Therefore, the relationship between the low voltage areas and conduction velocity in the AFL circuits has not yet been described.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25) The voltage reduction primarily originated from the ablative tissue injury and also the change in the activation rhythm. 12) In this study, we sampled the electrogram voltage along the ablation line. The results demonstrated that a greater reduction in the voltage was observed at the mid CTI ablation.…”
Section: Electrogram Voltage Reduction After Radiofrequency Ablationmentioning
confidence: 99%
“…9,10) Recently, a non-contact mapping (NCM) system has helped to determine the three-dimensional location of the ablation lesion accurately and reconstructs local virtual unipolar electrograms. 11,12) Therefore, a comparison of the local electrograms at the same sites is possible and can be used to evaluate the effect of acute ablative atrial tissue injury and to detect complete CTI block by the local electrogram voltage and the morphologic characteristics. Therefore, the purpose of this study was to investigate the voltage and the characteristics of the local virtual unipolar electrograms after radiofrequency ablation (RFA) of the CTI in patients with typical AFL using non-contact mapping system.…”
Section: Introductionmentioning
confidence: 99%